External Evaluation of Rashtriya Baal Swasthya Karyakram (RBSK) in Chhattisgarh & Practical Recommendations: External Evaluation of RBSK in Chhattisgarh (GAIMS Journal of Medical Sciences, 2023)
Context: Government of India launched the Rashtriya Bal Swasthya Karyakram (RBSK) for screening children from 0 to 18 years for 4 D’s (Defects, Diseases, Deficiency and Developmental Delays including disabilities) for timely referral and treatment. There are few studies published evaluating the implementation of this programme.Aims: To evaluate implementation of RBSK programme in Chhattisgarh state, problems in RBSK referral-to-treatment process.Methodology: One good performing district (Raigarh) and one poor performing district (Raipur) were selected, one block was randomly selected by lottery method from one rural and one urban area of each district respectively and all Mobile Health Teams (MHTs) of selected block were included for assessment. Since there are two MHTs allotted in each block, total 8 MHTs were evaluated. A pretested questionnaire was used to assess Knowledge, Attitude and Practice (KAP) of MHT doctors. Evaluation plan included health check-up of randomly selected students, interview with beneficiaries and visit to DEIC. Data analysis was done using Microsoft excel and SPSS.Results: There is shortage of manpower, screening equipment and reporting formats. KAP assessment of MOs shows below average information about paediatric conditions especially group A & D. Limited higher government centres for treatment of group A & D conditions (e.g. CHD, vision impairment, disability, etc.) leads to long waiting list, demotivation and loss to follow up.Conclusions: RBSK programme has its inherent strengths. Troubleshooting of vital issues will help in its smoother implementation. Introduce separate window/desk “CHIRAYU KHIDKI” at Medical College to fast-track service provision to children referred through RBSK. Provide specialised investigations free to beneficiary. Establish referral to centres providing rehabilitation to children with special needs and their care-givers.